How to implement policy: Coping with ambiguity and uncertainty. (28th October 2020) - Fowler, Luke
Abstract: The author examines policy implementation as an exercise in coping with ambiguity (i.e., different ways of thinking about the same issues) on the one hand and uncertainty (i.e., lack of information) on the other. Functions are how implementers figure out the best way to make a policy work in practice and processes are how organizations formalize mechanisms that make behaviours more predictable. Using programme evaluation data from the US Environmental Protection Agency (EPA) and a mixed methods approach, findings identify specific implementation activities associated with both functions and processes and, while intertwined, these represent two distinct aspects of operationalizing policies. Conclusions suggest guidance on how to cope with ambiguity and uncertainty in practice, and connect functional and policy capacities to key avenues of public policy and administration scholarship.